The Routledge Companion to Accounting Information Systems. (Routledge companions in business, management and accounting., 2017)
Information technology has permeated all walks of life in the past two decades. Accounting is no exception. Be it financial accounting, management accounting, or audit, information technology and systems have simplified daily tasks and routine work, simplified reporting, and changed how accounting is done. The Routledge Companion to Accounting Information Systems provides a prestige reference work which offers students and researchers an introduction to current and emerging scholarship in the discipline. Contributions from an international cast of authors provides a balanced view of both the technical underpinnings and organisational consequences of accounting information systems. With a focus on the business consequences of technology, this unique reference book will be a vital resource for students and researchers involved in accounting and information management.